Quantum confinement in multi-nanolayer sandwich systems - Khmelinskii, Igor (2019)
Presently we explored quantum confinement (QC) in three-nanolayer sandwich systems, composed of Au-SnO2-Fe, Au-SnO2-Si and Au-SnO2-Ag layers. We recorded the absorption spectra of these sandwich systems, all with discrete structure. We recorded the action spectra of the photocurrent for the Au-SnO2-Fe sandwich system, with the photocurrent quantum yields increasing with the photon energy, achieving 3.1 at 4.7 x 10(4) cm(-1). The photocurrent action spectra correlate with high accuracy with optical absorption spectra. We discuss the mechanisms determining the absorption bandwidth value, including surface imperfections, thermal distribution of the vibrational level populations in the electronic ground state, and the diabatic coupling of levels of the excited state to those of a "dark" state. Volt-Ampere (V/A) characteristics were recorded for all three of the sandwich systems, quite similar to those of a Schottky diode. We report the parameter values of the V/A characteristics, found by fitting the experimental data with a theoretical curve. We also report charge density changes in the SnO2 layer caused by low constant voltage applied to the sandwich structure, observed as changes in the absorption band intensity.